2017
DOI: 10.3126/kumj.v13i4.16834
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in Medical students and its correlation with cardiovascular risk factors: Emergency Alarm for Today?

Abstract: BackgroundIt is predicted that the prevalence of overweight and obesity will rise significantly by 2015 in young population. Problem of overweight and obesity has been recognized as public health problem worldwide due to the fact that it increases the risk of chronic diseases such as Cardiovascular Diseases (CVD), stroke, diabetes, sleep apnoea, osteoarthritis etc. ObjectiveTo assess the body mass index in medical students and its association with various cardiovascular risk factors like blood pressure, dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…The study is similar to studies done earlier which have reported similar correlation between BMI and blood pressure. 26,27 The results may be explained on the basis that with increase in BMI there is increase in sympathetic nervous system activity, endothelial dysfunction and increase in cytokines. 28 Limitation of this study analysis of dietary habits, physical activities and stress faced by the students will yield better results.…”
Section: Resultsmentioning
confidence: 99%
“…The study is similar to studies done earlier which have reported similar correlation between BMI and blood pressure. 26,27 The results may be explained on the basis that with increase in BMI there is increase in sympathetic nervous system activity, endothelial dysfunction and increase in cytokines. 28 Limitation of this study analysis of dietary habits, physical activities and stress faced by the students will yield better results.…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies that calculated BMI of medical students have been conducted in India, Pakistan, Poland, United Arab Emirates and Greece. [8][9][10][11] Amatya et al 12 in their study found that 18.31% medical students underweight, 77.18% normal, 4.23% overweight, and 0.3% obese (one male student).…”
Section: Discussionmentioning
confidence: 99%
“…3 Sebanyak 54,40 % siswa menyukai makanan siap saji (fast food) dan lebih dari 60% siswa tidak menyadari mengenai fakta bahwa makanan siap saji (fast food) adalah makanan yang tidak sehat. 4 Hasil survei yang dilakukan oleh Lemia dan Dalal (2019) Penelitian ini dapat dijadikan sebagai masukan dan bahan untuk penelitian selanjutnya, peneliti selanjutnya juga dapat melakukan intervensi dan mengembangkan penelitian ini mengenai konsumsi makanan siap saji pada siswa di SMA Negeri X Jakarta.…”
Section: Pendahuluanunclassified